Kriminalitas Tokoh Winarsih dalam Novel 5 Kelopak Mawar Berbisa Karya Ria Jumriati - Windusiyam, Puspita - (BASINDO : jurnal kajian bahasa, sastra Indonesia, dan pembelajarannya, 2020)
The study describes the crime committed by the Winasih figure in the novel 5 Venomous Rose Petals By Ria Jumiati. This study uses a qualitative approach. This study produced three conclusions, namely (1) the form of criminal acts of fogures, (2) the cause of criminal acts of figures, (3) the impact caused in the form of psyhological condition on the chaacter.